A novel multimedia interactive application to support road safety education among primary school children in Malaysia - Norkhairani, Abdul Rawi; Abd.Rasid, Mamat; Maizan, Mat Amin (Penerbit UTM Press, 2015)
The interactive multimedia is considered as a very promising potential to aid primary school pupils in learning and teaching method in introducing road safety education. Although web based applications for road safety education are available, they are based on overseas countries where the rules and environment settings are different from Malaysia’s environment. An effort to help pupils in interactively learning on road safety education in Malaysia has motivated this study. A framework encompass of learning theories, modules, multimedia elements and, usability and acceptance, has been developed and applied in an interactive multimedia prototype on road safety education called “FIQIR Road Safety”. The prototype has been developed based on a primary school textbook “Cermat Tiba Selamat” by Malaysian Ministry of Education (MOE). FIQIR Road Safety has been designed and developed by utilizing multimedia elements to give an immersive experience to the user. It employs Watch, Learn and Play as the modules where the animations and activities represent actual traffic environment in Malaysia. The proposed framework hopefully can be a guide in developing interactive multimedia application such as FIQIR Road safety.